Ancient Israel's faith and history an introduction to the Bible in context - Mendenhall, George E. 1916-; Herion, Gary A. (Louisville, KY Westminster John Knox, 2001)
Contents : The world from Abraham to Moses : prologue to the emergence of the biblical tradition -- Moses and the Exodus : the formative period of the biblical tradition -- The twelve-tribe federation : the adaptive period (I)-- Yahweh becomes king of Israel -- King David and the transition to monarchy : the adaptive period (II)-- the abdication of Yahweh -- The legacy of King Solomon : the traditional period (I)-- Yahwism versus Yahwisticism -- Josiah reforms the imperial religion : the traditional period (II)-- the troubling legacy of the monarchy -- Destruction and exile : the creative reform of Yahwism -- Jesus and the New Testament reformation : the renewal of an old faith. Includes bibliographical references, indexes, illustrations, maps, etc.
Keywords: Bible -- history of contemporary events -- textbooks